Cholinergic Modulation of Fast Inhibitory and Excitatory Transmission to Pedunculopontine Thalamic Projecting Neurons - Ye, Meijun (American Physiological Society, 2010)
The pedunculopontine nucleus (PPN) is part of the cholinergic arm of the reticular activating system, which is mostly active during waking and rapid-eye movement sleep. The PPN projects to the thalamus and receives cholinergic inputs from the laterodorsal tegmental nucleus and contralateral PPN. We employed retrograde labeling and whole cell recordings to determine the modulation of GABAergic, glycinergic, and glutamatergic transmission to PPN thalamic projecting neurons, and their postsynaptic responses to the nonspecific cholinergic agonist carbachol. M2 and M4 muscarinic receptor-modulated inhibitory postsynaptic responses were observed in 73% of PPN output neurons; in 12.9%, M1 and nicotinic receptor-mediated excitation was detected; and muscarinic and nicotinic-modulated fast inhibitory followed by slow excitatory biphasic responses were evident in 6.7% of cells. A significant increase in the frequency of spontaneous excitatory postsynaptic currents (EPSCs) and inhibitory postsynaptic currents during carbachol application was observed in 66.2% and 65.2% of efferent neurons, respectively. This effect was blocked by a M1 antagonist or nonselective muscarinic blocker, indicating that glutamatergic, GABAergic, and/or glycinergic neurons projecting to PPN output neurons are excited through muscarinic receptors. Decreases in the frequency of miniature EPSCs, and amplitude of electrical stimulation-evoked EPSCs, were blocked by a M2 antagonist, suggesting the presence of M2Rs at terminals of presynaptic glutamatergic neurons. Carbachol-induced multiple types of postsynaptic responses, enhancing both inhibitory and excitatory fast transmission to PPN thalamic projecting neurons through muscarinic receptors. These results provide possible implications for the generation of different frequency oscillations in PPN thalamic projecting neurons during distinct sleep-wake states.